Analisis Tingkat Literasi Keuangan Guru Dan Persepsinya Terhadap Pendidikan Literasi Keuangan : Studi Kasus Di RA 04 Cempaka Putih Kota Batu - firdiansyah, yhadi; Julaihah, Umi; Fitriah, Nurlaeli (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to analyze the level of financial literacy and teachers' perceptions of financial literacy education. This study uses a descriptive quantitative approach, this study involved 11 teachers as respondents. Data were collected through a questionnaire adopted from the developed instrument. The results of the study indicate that the level of financial literacy of teachers is quite good. The majority of teachers understand the importance of insurance for future protection and carry out regular savings activities. However, it was found that teachers lack confidence in comparing prices when making transactions. Regarding perceptions of financial literacy education, teachers generally agree that financial literacy learning is important to be taught from an early age and can have a significant impact on the quality of life in the future. This study also revealed that teachers want a curriculum that accommodates financial literacy learning for early childhood, and emphasizes the importance of cooperation between teachers, schools, and parents in developing children's financial literacy skills. In conclusion, although the level of financial literacy of teachers is quite good, improvements are still needed in several aspects, especially in the ability to compare prices. In addition, a more comprehensive curriculum is needed to support financial literacy education from an early age